Progress in structure-based drug development targeting chemokine receptors - Wang, Jin; Qu, Chen; Xiao, Peng; Liu, Sijin; Sun, Jin-Peng; Ping, Yu-Qi (Frontiers in Pharmacology, 2025)
As a critical subfamily of G protein-coupled receptors (GPCRs), chemokine receptors (CCRs) play pivotal regulatory roles in immune cell migration, inflammatory modulation, tissue regeneration, and tumor microenvironment (TME) remodeling. By specifically recognizing chemokine ligands, CCRs orchestrate immune cell trafficking and tissue positioning, with functional dysregulation implicated in infectious diseases, autoimmune disorders, neurodegenerative pathologies, and cancer. These receptors thus represent promising therapeutic targets. Recent breakthroughs in cryo-electron microscopy (cryo-EM) and computational chemistry have enabled high-resolution structural analysis and dynamic conformational modeling of CCRs, establishing a robust foundation for structure-based drug design (SBDD). This review synthesizes current advances in CCR biology, structural mechanisms, disease involvement, and targeted drug development, providing theoretical insights and technical frameworks for future research.